Size-transformable nanostructures : from design to biomedical applications - Zhang, Xiaodong (2021)
The size of nanostructures (NSs) strongly affects their chemical and physical properties and further impacts their actions in biological systems. Both small and large NSs possess respective advantages for disease theranostics, and this therefore presents a paradox when choosing NSs with suitable sizes. To overcome this challenge, size-transformable NSs have emerged as a powerful tool, as they can be manipulated to possess the merits of both types of NSs. Herein, various strategies to construct size-transformable NSs are summarized, and the recent research progress regarding their biomedical applications, particularly within the fields of cancer and bacterial theranostics, is highlighted. This review will inspire researchers to further develop various methods that can be used to construct size-transformable NSs for use in novel applications within different fields.